Obtencion de aductos de aflatoxina B1-guanina - Mella, C.=700 1 Escobar, A.; Noa, M.; Acosta, A.
(Es, En)
Ilus., 8 ref.
Keywords: AFLATOXINAS; GUANINA; SUSTANCIAS TOXICAS; CONTAMINACION QUIMICA; PIENSOS; GANADO BOVINO; IDENTIFICACION; CUBA